The intermittent nature of player physical output in professional football matches: An analysis of sequences of peak intensity and associated fatigue responses - Schimpchen, J.; Gopaladesikan, S.; Meyer, T. (European Journal of Sport Science, 2021)
Professional footballers experience transient periods of in-game fatigue which might affect match outcomes. Further information regarding the degree of fatigue elicited by periods of peak physical intensity across different movement metrics is needed to allow for a more informed design of targeted training interventions. To that end, the purpose of this study was to identify sequences of player peak physical output in-game for three different rolling time windows (1-, 5-, 10-minutes) across three movement categories (total distance, high-intensity distance, average acceleration/deceleration) for 29 players during a full season of professional football matches. Physical performance was also assessed for the 5-minutes after peak intensity to identify possible signs of acute fatigue, while goal differential and match time were registered as contextual variables to analyse whether peak physical output fluctuations were game-state dependent. Total distance and average acceleration/deceleration were reduced by 11%-18% in the first minute after peak intensity but returned to match average within the third minute. High-intensity distance remained reduced by 64%-89% from the first minute after peak intensity to 6%-31% at the fifth minute after. Both contextual factors had an influence on players` ability to perform at peak intensity, but only when considering total distance and average acceleration/deceleration. In contrast, high-intensity distance peak performance remained unaffected by contextual factors. These findings indicate that player in-game fatigue is most pronounced after periods of peak high-intensity running, highlighting the need for targeted training interventions to minimise subsequent reductions in players` physical output capabilities.